Solar Panel Monitoring System with Microcontroller Based Data Storage - Junaidi, Andi; Yogianto, A. Agus; Setiawan, Denny; Naufal, Arga Rifqi (SOTVI, 2025)
Solar photovoltaic (PV) systems have been widely implemented in diverse applications, including buildings, traffic light systems, and public infrastructure, to reduce reliance on fossil fuels. However, the effectiveness of these systems depends on detailed and user-friendly monitoring, which remains a challenge due to cost and complexity barriers. This study addresses this gap by developing a low-cost, scalable PV monitoring system that integrates microcontroller-based sensors and data loggers to measure current, voltage, and power output in real time. The system is designed to be easily deployable and accessible, enabling broader adoption for renewable energy management. Using an experimental methodology, the system’s accuracy was validated through voltage sensor error analysis, yielding an average error of 0.07%, demonstrating high precision. The proposed solution not only enhances monitoring capabilities but also contributes to the optimization of solar energy systems by providing reliable data for performance evaluation. This research underscores the potential of affordable monitoring tools to support the sustainable expansion of solar PV technology.